Image Methods, Verbal Symbolism, Demonstrations And Visuals In The Texter Of The Qur'an - Asep Saepulloh; Fitry Liana; Tatang Abdul Basir; Mastuhi Mastuhi (Edumaspul: Jurnal Pendidikan, 2022)
The Qur'an was sent down to understand the instructions for humans towards clear goals and straight paths by upholding the principles of life based on faith. The purpose of this study is to analyze the method of interpreting the Qur'an by parable, verbal symbolism, demonstrations, and visuals in the Qur'an. The research method used is library research. The results of the study show that Majaz is using lafadz to mean something other than the original meaning because it has something to do with the original meaning and there is a qorinah that points to it. For example, using the word "lafadz asad" not for wild animals, namely lions, as the original meaning, but for "rajulun suja" (a brave man), because there is a relationship between them being brave. Majaz can be related to words independently, such as the word "asad," which has its meaning transferred from an animal called "king of the jungle" to mean a brave person, or the attribution of an activity, or something similar to it, to something other than the perpetrator because of a connection with him. Meanwhile, verbal communication is communication that uses verbal symbols, both orally and in writing. Symbols or verbal messages are all kinds of messages that use one or more words.